Interpreting discordance on dual-tracer positron emission tomography–computed tomography in the setting of metastatic neuroendocrine tumor: Detection of metachronous triple-negative breast carcinoma - Kalshetty, Ashwini; Basu, Sandip (World Journal of Nuclear Medicine, 2020)
Second primary malignancies (SPMs) are known to be associated with neuroendocrine tumors (NETs). The association necessitates a careful assessment of the dual-tracer positron emission tomography–computed tomography (PET-CT) imaging findings to identify these malignancies earlier. Such early diagnosis can provide incremental benefit for screening these SPMs apart from their known applications in the management of NETs. A case of incidentally detected metachronous triple-negative breast carcinoma on dual-tracer PET-CT imaging is presented using 18fluoro-2-deoxy-D-glucose (FDG) and 68Ga-DOTATATE that showed a high uptake on FDG but no uptake on somatostatin receptor-based imaging.
Keywords: 68Ga-DOTATATE; dual-tracer positron emission tomography–computed tomography; fluoro-2-deoxy-D-glucose positron emission tomography–computed tomography; metastatic neuroendocrine tumors; triple-negative breast carcinoma